مدى تأثير سياسة التحفظ المحاسبي على إتخاذ القرارات في ظل التقلبات الاقتصادية في القطاع المصرفي السوداني - عمر, وليد الطيب; سليمان, الطيب محمد (Gezira Journal of Economic and Social Sciences, 2020)
يعتبر التحفظ المحاسبي بأنه رد فعل حذر لضمان أن عدم التأكد والمخاطر الملازمة لمواقف الأعمال تم أخذها في الاعتبار بدرجة كافية وهو من المفاهيم الاساسية التي تؤثر بطريقة مباشرة على إعداد التقارير المالية وبالتالي اتخاذ القرارات، لذلك هدفت الدراسة الى معرفة أثر التحفظ المحاسبي على اتخاذ القرار  فى ظل التقلبات الاقتصادية التي تصاحبها حالات عدم التأكد وذلك بالتعّرف على حلقات الربط بين التقلبات الاقتصادية وأسباب استخدام سياسة التحفظ المحاسبي، وتحديد أثر هذه التقلبات الاقتصادية على ثقة مستخدمي البيانات المالية فى القطاع المصرفي بالسودان. ولتحقيق أهداف الدراسة استخدام المنهج الوصفي التحليلي وذلك من خلال توزيع استبانة على عينة عشوائية من المصارف السودانية لتغطية وجهة من المصار السودانية لتغطية وجهة نظر ثلاث وجهة نظر  ثلاث فئات (المدراء، ورؤساء الاقسام المالية، المراجعين)، وقد توصلت الدراسة الى عدة نتائج كان أبرزها، أن استخدام  التحفظ المحاسبي يُعد كدرع واقي، وقد أظهرت الدارسة أن المصارف السودانية في حالة عدم التأكد عند إعداد التقارير المالية خاصة فى ظل وجود اقتصاد متقلب وغير مستقر، كما يعمل على التخفيض من مخاطر انهيار المؤسسات المالية الناتجة عن سوء استخدام السياسات المالية في ظل الازمات المالية. وقد أظهرت الدراسة أن المصارف  السودانية تلتزم بسياسة التحفظ المحاسبي بدرجة عالية في اعداد التقارير المالية في ظل الأزمات المالية خاصة وأن تحوّل القطاع المصرفي السوداني من النظام المصرفي التقليدي الى النظام المصرفي الإسلامي أضاف أعباء جديدة فى تحديد مؤشرات قياس الأداء المالي للمصارف السودانية، وقد ساهم ذلك فى تقليل درجة عدم التأكد وتوجيه سلوك متخذي القرار، ومكّن القطاع المصرفي من التعامل مع التقلبات الاقتصادية فى السودان بدرجة كبيرة .وقد أوصت  الدراسة  بضرورة  أن تولي الجهات القائمة على تنظيم مهنة المحاسبة الاهتمام بمفهوم التحفظ المحاسبي من حيث الدلالة والمضمو.ن. وتنظيم معايير وإرشادات محاسبية واضحة لتنظيم العمل المحاسبي فى السودان، وتتيح سبل اختيار المستوى المناسب والمرغوب فيه من التحفظ المحاسبي. كذلك ضرورة الاستمرار فى سياسة التحفظ المحاسبي بقدر الامكان لتجنب التقلبات الاقتصادية والأزمات المالية التي تؤثر على كل مفاصل الاقتصاد السوداني   Accounting conservatism is considered as cautious reaction to ensure that uncertainty and business risk, which  have been taken sufficiently into consideration . it is  from the fundamental concepts that directly affects decision- making. The purpose of the study is to know the impact of accounting conservatism on the decision-making under uncertainty, by identifying the links between thee economic fluctuations and the reasons for using accounting conservatism and determining the impact of these economic fluctuations on the trust of financial statements users in the banking sector in Sudan. Descriptive analysis of data has been used, through the distribution of a questionnaire to a random sample of Sudanese banks covering three categories; the financial managers, department heads, and auditors. The study has reached several results, the most important of these is the use of the accounting conservatism as a shield to reduce the uncertainty in the preparation of financial reports, especially in light of a volatile and unstable economy, and works to reduce the risk of collapse of financial institutions resulting from misuse of accounting policies during the financial crises. The study showed that the Sudanese banks adhere to the policy of accounting conservatism in a high degree in the preparation of financial reports during the financial crises, especially as the Sudanese banking system was shifted from traditional banking system  to  Islamic banking and the system, which added new burdens in determining indicators of financial performance measurement of Sudanese banks. These has contributed to reduce the degree of uncertainty, guide the behavior of decision makers and enabled the banking sector to deal with economic fluctuations. The study recommended that bodies regulating the accounting profession should focusing on the concept of the accounting conservatism in terms of significance and content, and organizing clear accounting standards and guidelines to regulate the accounting work in Sudan. It also provides the means to choose appropriate and desirable level of accounting conservatism, as far as possible to avoid economic fluctuations and financial crises affecting all aspects of the Sudanese economy